“¿Son nuestras muertes merecedoras de dignidad?” - Robles-Moreno, Leticia (2024)
Germain Machuca is a Peruvian performance artist and activist, whose work for LGTBIQ+ rights has tirelessly demanded more humane politics towards communities living with HIV/AIDS. They have performed artistic protests against Peruvian state violence toward the most vulnerable populations: Indigenous, racialized, marginalized, and queer/cuir bodies. Germain’s work centers on bodily narratives that emerge from personal explorations in dialogue with a myriad of marginalized and stigmatized bodies rendered disposable by the state. Both in performance spaces and in the streets, Germain offers their body to ask who has the right to dignity after death. In their performance work, Germain intertwines contemporary body art explorations and research of pre-Hispanic traditions and Andean cultural expressions. Their body is at the center of their creative process, highlighting the intersections of gender, sexuality, and race. The characters, or more accurately, avatars that emerge in Germain’s performances wear drag-style make-up, platform shoes, and lingerie. The bare portions of their body are open to be touched by the audience, who are invited to acknowledge a racialized presence that makes visible those Indigenous-mestizo queer bodies marginalized by the Peruvian government and society at large. At the same time, these avatars sometimes don traditional masks that have been part of Andean festivals for centuries, or dialogue with Indigenous cultural expressions that were proscribed as part of the colonial project of erasure and control. In this sense, Germain’s body traces connections between current systems of oppression that target queer, Brown, disenfranchised bodies, and the history of colonization in the Americas.